Kemampuan Pedagogical Content Knowledge (PCK) Guru IPA SMP Negeri Se-Kecamatan Jatisrono Dalam Menyusun RPP Tahun Ajaran 2016/2017 - Arifah, Miftah; , Dra. Hariyatmi, M. Si (2017)
Teachers as professional educators are the main components that determine the success of an education. The purpose of this study is to determine the Pedagogical Content Knowledge (PCK) capability of scince teachers Jatisrono High School in Arranging the Lesson Plan 2016/2017 academic year. The type of this research is qualitative descriptive with random sampling technique. Sampling technique in this research includes identification, tabulation, and description of lesson plan of science teacher. The population in this study were 17 science teachers with a sample of 15 teachers who contributed 52 lesson plan. Lesson plan identification results showed good CK ability (61.8%), good PK ability (76.2%), and excellent PCK ability (80.5%). Based on the research that has been done can be concluded that the ability of PCK science teachers in junior high schools in Jatisrono in preparing lesson plan academic year 2016/2017 very good (80.5%).